PENGARUH KONDISI SOSIAL EKONOMI MASYARAKAT TERHADAP POLA PEMAKAIAN AIR DOMESTIK - Benny Syahputra (Universitas Islam Sultan Agung, 2022)
The development of the socio-economic conditions of the community can affect the use of domestic water in an area. The purpose of this study was to determine the domestic water demand in the Kalasan Subdistrict at different social and economic levels. The method used in this study includes interviews to collect data based on stratified proportional random sampling. This study obtained the results, namely: (1). The level of education in Kalasan Subdistrict affects the use of domestic water, this shows that the higher the level of education, the greater the use of water, so the higher education level tends to use water more wastefully; (2). Income level does not affect domestic water use; (3). The use of domestic water in the Kalasan Subdistrict is not determined by certain types of work.